North Korean Economy: A Historical Assessment - Chun, Hong Tack; Park, Jin (The Korean Economy 1945-1995: Performance and Vision for the 21st Century, 1997)
Part Five (Chapter 16)presents a historical review of North Korea`s economic system and policies together with its performances. Analyzing the causes of its economic plight in the 1990s, the authors also suggest a direction for the reforms required to improve its economic situation.